More Than a Device: Function Implementation in a Multi-Gate Junctionless FET Structure - Hossain, Sehtab; Iqbal, Md Arif; Samant, Prerana; Siddiki, Mahbube K.; Rahman, Mostafizur (Journal of Electronics and Electrical Engineering, 2023)
The miniaturization of transistor sizes to keep up with Moore’s Law in Integrated Circuits (ICs) is rapidly approaching physical limits. To extend Moore’s Law, single-device-based computing shows promise by achieving more functionality in a smaller footprint. However, existing approaches either embed only primitive logic, leading to inefficient performance, or rely on exotic devices that require costly non-conventional fabrication. Previously, we introduced Crosstalk Computing, which leverages deterministic signal interference between nano-metal lines for logic computation. This paper elaborates on realizing complex Boolean functions through TCAD-based modeling and simulations, using a multi-gate Junctionless FET-based device with independent gates. We demonstrate the implementation of various complex logic functions alongside primitive gates, achieving an average of 8× density improvement and 8× lower power consumption compared to CMOS-based implementations. Delay characteristics are comparable to 14 nm PTM counterparts. This standalone device approach is compatible with existing fabrication processes.